Challenges of Conducting Contingent Valuation Studies in Developing Countries. (18th December 2015) - Durand-Morat, Alvaro; Wailes, Eric J.; Nayga, Rodolfo M.
Abstract : We review the experiences and challenges that researchers can face when conducting contingent valuation studies in developing countries. We discuss these challenges based on our own experiences of conducting field‐contingent valuation studies about genetically modified rice in five developing countries that represent different regions of the world and diverse cultures; we also base our discussion on results from a survey we conducted of agricultural and applied economists regarding their own experiences. The issues covered include the selection and training of local personnel, the recruitment of participants, sampling challenges, participants' compensation, survey methods and implementation, elicitation methods, the literacy rate of the population, and security/safety issues in developing countries. We also discuss the implications of our findings to other well‐established stated‐preference methods such as choice experiments.